Alignment of vector fields on manifolds via contraction mappings - O.N. Kachan; Yu.A. Yanovich; E.N. Abramov (Учёные записки Казанского университета: Серия Физико-математические науки, 2018)
According to the manifold hypothesis, high-dimensional data can be viewed and meaningfully represented as a lower-dimensional manifold embedded in a higher dimensional feature space. Manifold learning is a part of machine learning where an intrinsic data representation is uncovered based on the manifold hypothesis.